1999
DOI: 10.1046/j.1365-2133.1999.03100.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for management of Bowen's disease

Abstract: These guidelines for management of Bowen's disease have been prepared for dermatologists on behalf of the British Association of Dermatologists. They present evidence-based guidance for treatment, with identification of the strength of evidence available at the time of preparation of the guidelines, and a brief overview of epidemiological aspects, diagnosis and investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
0
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 87 publications
3
152
0
11
Order By: Relevance
“…Due to inconsistencies of different treatment regimens used at different centres, their relative comparison for effectiveness is difficult as published data do not fully control for factors such as size and site. A useful modality of treatment, especially in small lesions over the sites which have a delayed healing, perineal lesions, and digital lesions is surgical excision 4,11 . Various studies have demonstrated an early 100% cure rate for surgical excision, as was seen in a clinicopathological study of 47 cases of perianal Bowen's disease excision by Marchesa et al 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to inconsistencies of different treatment regimens used at different centres, their relative comparison for effectiveness is difficult as published data do not fully control for factors such as size and site. A useful modality of treatment, especially in small lesions over the sites which have a delayed healing, perineal lesions, and digital lesions is surgical excision 4,11 . Various studies have demonstrated an early 100% cure rate for surgical excision, as was seen in a clinicopathological study of 47 cases of perianal Bowen's disease excision by Marchesa et al 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Usually BD is a solitary lesion, but in 10% to 20% of cases, it occurs at multiple sites 1,2 . 3% to 5% of extragenital lesions and about 10% of genital lesions may progress into an invasive carcinoma 3,4 . In the Caucasian population, BD is quite commonly seen, with an incidence of 1.42 per 1000 in some populations 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Wahl bei klei nen, so li tär-en M. Bo wen ge se hen [5]. In ei ner re trospek ti ven Stu die wur de eine Re mis si ons rate von 93 mit die sem Ver fah ren er reicht [3], teil wei se wird die Hei lungs ra te mit bis zu 98 an ge ge ben.…”
Section: Kü Ret Ta Geunclassified
“…Die Kryo the ra pie, Ex zi si on, Kü ret ta ge mit Elek tro kau ter, La ser be hand lung, 5-FU und PDT wei sen bei der The ra pie des M. Bo wen alle ähn li che Re zi divra ten von 5-10 auf, und kei ne The ra piemög-lich keit ist für alle kli ni sche Si tua tio nen den an de ren über le gen [5].…”
Section: Aus Wahl Der the Ra Pie Artunclassified
See 1 more Smart Citation